(untitled) (Albayan Scientific Journal, 2023)
The purpose of this study was to determine the impact of HRM practices on employee’s performance in the company of Hatif Libya in the city of El-Beida. Random sampling technique was used to collect data for this study. A questionnaire based on (39) items was distributed among (78) employees of Hatif Libya for data collection. The statistical software package (SPSS 22) was used to analyze the data. To check the association between HRM practices and employee’s performance, Pearson correlation coefficient and regression analysis was applied on the data. The results indicate that HRM practices, which were represented in: Compensation system, Performance appraisal, Selection and appointment, and Training and development have a positive impact on employee’s performance. Hence, it is proved that independent variables contribute positively towards change in the dependent variable. Finally, the study suggested some recommendations that could realize improvement in employee performance in company of Hatif Libya in particular and other companies in general.